2003
DOI: 10.1038/sj.onc.1206755
|View full text |Cite
|
Sign up to set email alerts
|

BCL6 overexpression prevents increase in reactive oxygen species and inhibits apoptosis induced by chemotherapeutic reagents in B-cell lymphoma cells

Abstract: Chromosomal translocations and somatic mutations occurring in the 5 0 noncoding region of the BCL6 gene, encoding a transcriptional repressor, are most frequent genetic abnormalities associated with non-Hodgkin B-cell lymphoma and result in deregulated expression of BCL6. However, the significance of deregulated expression of BCL6 in lymphomagenesis and its effect on clinical outcomes of lymphoma patients have remained elusive. In the present study, we established Daudi and Raji B-cell lymphoma cell lines that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 40 publications
6
81
0
Order By: Relevance
“…30 To examine whether this is the case in HL, Bcl-6 expression levels were examined in ROS-high and -low L1236 and L428 cells. No significant difference in Bcl-6 expression was detected between these two populations, indicating that Bcl-6 was not involved in the regulation of ROS production, at least in L1236 and L428 cells (Figure 4e).…”
Section: Tumorigenic Population In Hodgkin Lymphoma J-i Ikeda Et Almentioning
confidence: 99%
“…30 To examine whether this is the case in HL, Bcl-6 expression levels were examined in ROS-high and -low L1236 and L428 cells. No significant difference in Bcl-6 expression was detected between these two populations, indicating that Bcl-6 was not involved in the regulation of ROS production, at least in L1236 and L428 cells (Figure 4e).…”
Section: Tumorigenic Population In Hodgkin Lymphoma J-i Ikeda Et Almentioning
confidence: 99%
“…Apoptosis and Dc m were analysed by flow cytometry as described previously (Kurosu et al, 2003). In brief, cells were stained with Annexin V-FITC and propidium iodide (PI) using the TACS Annexin V Kit (Trevigen, Gaithersburg, MD, USA) and analysed using a Becton Dickinson FACSscan flow cytometer (Mountain View, CA, USA) for apoptosis.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
“…Analyses of ROS and MMP Intracellular ROS levels were measured fluorometrically using a fluorescent probe, HE, which is oxidized to the fluorescent intercalator ethidium by cellular oxidants, particularly superoxide radicals (Rothe and Valet, 1990), as described previously (Kurosu et al, 2003). In brief, 1 Â 10 6 cells were incubated with 2 mM HE for 30 min at 371C, resuspended in phosphatebuffered saline (PBS), and analysed by flow cytometry.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
“…60 An increase in its expression can inhibit the apoptosis of lymphoma cells treated with chemotherapeutic reagents, most likely through enhancement of the antioxidant defense systems. 55 It is also indicated that inhibition of Bcl-6 function by a dominantnegative form of Bcl-6 can inhibit the cell cycle progression and induce apoptosis in Raji cells. 61 Previous studies showed that the activation of peroxisome proliferator-activated receptor (PPAR)-d increased both total and free Bcl-6 levels and inhibited the activation of p38 and ERK1/2, 62 and the activated form of p38 was detected in spermatocytes of adult Bcl-6-deficient mice.…”
Section: Discussionmentioning
confidence: 99%